ANALISIS TINDAK TUTUR DIREKTIF BERBAHASA LAMPUNG ANAK USIA 10 TAHUN DALAM INTERAKSI KELUARGA DI LIWA - Reza, Muhammad Arfa; Damayanti, Dwi; Prayogi, Rahmat (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2025)
Speech act is a linguistic action used by someone to convey a message. The first and most influential environment in a social learning process is the family environment, especially parents through interpersonal communication. Our research aims to identify and analyze the forms of directive speech acts commonly used by children towards parents in the context of family communication in Lampung language in Kesugihan Baru Village, Liwa, West Lampung. This research uses descriptive qualitative methods through observation and interviews. In this study, we found four types of directive speech acts used by children: requests, orders, prohibitions, and advice. These utterances appear in various everyday situations and are influenced by emotional closeness and the context of interaction. The results of the study show that children are able to use language pragmatically to express their desires and influence their parents' actions effectively. This phenomenon is interesting to study, especially since there is still very little research on how children use Lampung regional language to influence their parents' actions from a pragmatic perspective.